The Effects of MAPP and OPDC on Physical and Mechanical Properties of OPDC-RPC / Muhammad Aqif Adam...[et al.] - Adam, Muhammad Aqif; Sulaiman, Alawi; Abd Pahmy, Nur Fitrah Aqilah; Mokhtar, Mohd Noriznan; Tabatabaei, Meisam; Subbian, Karuppuchamy (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Oil palm decanter cake reinforced with polypropylene composite (OPDC-RPC) was developed by varying the percentages of oil palm decanter cake (OPDC) and maleic anhydride polypropylene (MAPP). By adding MAPP, the mechanical properties (tensile, flexural and impact strength) had improved and the optimum mechanical strength was obtained at 30% OPDC due to strong internal bonding of OPDC and polymer. This evidence was captured using SEM where OPDC had a better bonding with MAPP. Water absorption test also confirmed the nature of hydrophilic properties of OPDC. To reduce the water absorption, MAPP was added and able to reduce the void inside OPDC-RPC material, hence reduced water penetration and water absorption rate.